Kelayakan Investasi Usaha Ayam Broiler Sistem Closed House Dan Open House Di Kabupaten Madiun - Fadhlurrohman, Muhammad Surya; Kilat Adhi, Andriyono; Nurmalina, Rita (Magister Science of Agribusiness, Department of Agribusiness, FEM-IPB University, 2024)
Animal protein is a protein that is good for the growth of the human body. Broiler chicken is one source of protein that is often consumed. Broiler production in Madiun Regency is insufficient, so it is necessary to increase production through broiler farming. This study aims to identify the feasibility of broiler business investment. The research location was in Madiun Regency and the research was conducted in March-December 2023. The research was conducted in Madiun District by taking 30 respondents from closed house and open house cage system farms. The non-financial feasibility analysis used market aspects, technical aspects, management and legal aspects, social, economic and cultural aspects, environmental aspects. Based on non-financial aspects, closed house and open house cages have not fulfilled the environmental aspects and the location of the cages is too close to residential areas. Therefore, farmers must maintain the cleanliness of the cage so as not to disturb residents around the cage. Financial analysis uses NPV, IRR, Net BC, PP and switching value sensitivity analysis. The results of the financial analysis found that in scenario I the closed house and open house cage systems were feasible. In scenario II, the closed house system is feasible and the open house system is not feasible. The results in both scenarios show that the closed house system has a better feasibility value, so the closed house system is more financially profitable than the open house.The results of the switching value sensitivity analysis of both types of cages have the most sensitive changes to the business in the form of decreased production, decreased prices and increased feed costs. Partnership system broiler farmers cannot regulate selling and feed prices, so the only way to keep the business viable is to maintain the resulting production. Therefore, farmers must be able to master good production management and cage management to produce maximum broiler production.